Hukum Islam, HAM dan Maqashidu Asy-Syari’ah: Upaya Menyatukan Jasad dan Ruh - Nahe’i Nahe’i (Program Pascasarjana Universitas Ibrahimy, 2019)
One debate that will not be finished is a debate about the relationship between human rights and Islam. Even though the Cairo Declaration was established which declared human rights in Islam and also declared the efforts to transform human rights into the National Law. It does not end, especially among